1994
DOI: 10.1007/bf00868269
|View full text |Cite
|
Sign up to set email alerts
|

HLA antigens in Arab children with steroid-responsive nephrotic syndrome

Abstract: Forty-eight Arab patients with steroid-responsive childhood nephrotic syndrome were studied for the frequency of HLA-A, -B, -C and -DR antigens. HLA-DR7 was significantly increased in the patient group (63% vs. 28%, P = 0.0002) confirming reports of a DR7 association in other ethnic groups and indicating a universal association with this antigen. HLA-CW6 was also significantly increased (44% vs. 21%, P corr. = 0.042). HLA-DQW1 was significantly reduced in the patients (29% vs. 57%, P corr. = 0.012) as was HLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
0
10
1
Order By: Relevance
“…In Caucasians, Egyptian and Kuwaiti children the HLA DR 07 was significantly more common in children with NS as compared to controls. However this was not observed in our study population as well as in Japanese and Chinese patients [2,9,11,13]. In Japanese children the allele HLA-DR8 was significantly more common [7].…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…In Caucasians, Egyptian and Kuwaiti children the HLA DR 07 was significantly more common in children with NS as compared to controls. However this was not observed in our study population as well as in Japanese and Chinese patients [2,9,11,13]. In Japanese children the allele HLA-DR8 was significantly more common [7].…”
Section: Discussioncontrasting
confidence: 79%
“…The etiological fraction of DQβ1*020X for patients with nephrotic syndrome in our study was moderate (0.381). The association with HLA-DQβ1*020X has been demonstrated in most previous studies in children from different ethnic populations except in Japanese children, indicating a strong association with nephrotic syndrome [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In Caucasians, Egyptian and Kuwaiti children the HLA DR 07 was significantly more common in children with NS as compared to controls.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…There is a controversy regarding the association of HLA class II antigens and childhood SR-MCNS. Many investigators [3,16,22,26] state that children with SR-MCNS do not exhibit any significant association with class II antigens. Meanwhile, Ruder et al [21] and Bouissou et al [2] reported that in children with SR-MCNS the only association is with the combined occurrence of HLA-DR3/DR7.…”
Section: Discussionmentioning
confidence: 98%
“…Again, there is no universal negative association between childhood PNS and HLA alleles. HLA-DQW1 antigen is reduced in Kuwaiti children with PNS [26]. Abe et al [27] reported a low frequency of DQA1*0103 in Japanese children with PNS.…”
Section: Discussionmentioning
confidence: 99%